1995
DOI: 10.1016/0009-9236(95)90051-9
|View full text |Cite
|
Sign up to set email alerts
|

Single- and multiple-dose pharmacokinetics of nefazodone in patients with hepatic cirrhosis

Abstract: These findings indicate that, although no untoward accumulation is anticipated compared with patients with normal hepatic function, patients with hepatic impairment may be exposed to higher concentrations of nefazodone and its metabolites than would subjects with normal hepatic function. Consequently, a lower daily dose of nefazodone should be considered when treating patients with impairment of hepatic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…It has been shown that nefazodone and these primary nefazodone metabolites undergo extensive metabolic clearance in humans via N-dealkalation, hydroxylation and conjugation reactions followed by urinary and fecal excretion [9,20]. Consistent with these findings are the results of single [7] and multiple-dose [21] studies which demonstrated that subjects with hepatic impairment exhibit increased systemic exposure and longer tl/2 values for NEF, HO-NEF and mCPR Subjects in the three treatment groups in the present study had normal liver function which, in the absence of an effect of renal impairment, explains why the pharmacokinetics of nefazodone and its two metabolites were comparable among groups. The lack of significant effect of renal impairment on systemic exposure or elimination of nefazodone and its metabolites is consistent with observations for other drugs which are eliminated mainly by hepatic metabolism, such as buspirone [22] and the selective serotonin reuptake inhibitor drugs, fluoxetine [23] and sertraline [24].…”
Section: Discussionsupporting
confidence: 81%
“…It has been shown that nefazodone and these primary nefazodone metabolites undergo extensive metabolic clearance in humans via N-dealkalation, hydroxylation and conjugation reactions followed by urinary and fecal excretion [9,20]. Consistent with these findings are the results of single [7] and multiple-dose [21] studies which demonstrated that subjects with hepatic impairment exhibit increased systemic exposure and longer tl/2 values for NEF, HO-NEF and mCPR Subjects in the three treatment groups in the present study had normal liver function which, in the absence of an effect of renal impairment, explains why the pharmacokinetics of nefazodone and its two metabolites were comparable among groups. The lack of significant effect of renal impairment on systemic exposure or elimination of nefazodone and its metabolites is consistent with observations for other drugs which are eliminated mainly by hepatic metabolism, such as buspirone [22] and the selective serotonin reuptake inhibitor drugs, fluoxetine [23] and sertraline [24].…”
Section: Discussionsupporting
confidence: 81%
“…However, one or more of these metabolites was absent in the plasma, urine or bile of SCID, PXB and Cyp3a KO mice (Table 1). Further, the exposure levels of NEF, OH-NEF and TD in clinical studies were reproduced in Cyp3a KO CM after a single oral administration of 10 mg/kg NEF [27,28]. Moreover, the UV chromatogram of the plasma of Cyp3a KO CM (Figure 2a) closely resembled a radiochromatogram of the pooled plasma samples taken 6-12 h after an oral administration of 14 C-nefazodone following a 14-day repeated administration of unlabelled nefazodone to healthy male volunteers ( Figure 6) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although nefazodone (NEF) has been used to treat major depressive disorders, the drug was withdrawn from the US market in 2004 due to hepatotoxicity. Of the human metabolites of the drug, hydroxynefazodone (OH‐NEF) and the triazoledione form of nefazodone (TD) are known to have pharmacological activity . p ‐Hydroxynefazodone ( p ‐OH‐NEF) is converted to the reactive quinoneimine , and m ‐chlorophenylpiperazine (mCPP) has depressive and anxiogenic effects in humans .…”
Section: Introductionmentioning
confidence: 99%
“…Offen bleibt jedoch die Frage, warum ein relativ neues Medikament, Nefazodon ist in Europa erst seit 1997, in den USA seit 1994 zugelassen, innerhalb eines so kurzen Beobachtungszeitraumes 7 schwere Leberversagen induziert hat. Mögli-cherweise birgt der komplizierte und verzweigte Abbauweg von Nefazodon mit nichtlinearer Pharmakokinetik und hoher interindividueller Plasmaspiegelvariabilität [3,4,19] die Gefahr von aberrierenden Metabolisierungswegen, deren klinische Auswirkungen schwer abschätzbar sind. In Anlehnung an die jüngst von der Arzneimittelkommission der deutschen Ärzteschaft herausgegebenen Mitteilungen [2] sollten daher nach Beginn der Einnahme von Nefazodon Leberenzymkontrollen in 4-bis 6-wöchigem Abstand über mindestens 12 Monate durchgeführt werden.…”
Section: Fazitunclassified
“…Nefazodon unterliegt einer exzessiven hepatischen Metabolisierung. Pharmakokinetisch nichtlinear erfolgt dort der Abbau zu den Metaboliten mCPP (Meta-Chloro-Phenylpiperazin), Hydroxynefazodon und Desmethylhydroxynefazodon (Triazoledion) [3].Pharmakologisch aktiv sind die Metaboliten mCPP und Hydroxynefazodon, beides gleichermaßen Abbauprodukte des verwandten Trazodon. Nefazodon, Hydroxynefazodon und ein weiteres durch Hydroxylierung entstehendes NefazodonDerivat inhibieren in klinisch relevanter Weise das Zytochromenzym P450 3A4.…”
Section: Introductionunclassified